Bioethics: Latin American Perspectives - Bertomeu, María Julia,; Salles, Arleen L.F., (Brill Book Archive Part 1, ISBN: 9789004472495., 2002)
This book presents a unique view of the current state of development of bioethics in Latin America. Twelve Latin American thinkers who share a primary interest in bioethics address a vast range of questions, including autonomy, rights, justice, and the role of culture and religion in bioethics. These studies contribute to an understanding of Latin American thought, and they make possible a transcultural dialogue on bioethical issues.